Female athlete triad in monozygotic twins - Hind, K.; Truscott, J.; Carroll, S. (The Physician and Sportsmedicine, 2008)
Female monozygotic twins, both international endurance athletes aged 18 years, presented for a dual energy x-ray absorptiometry (DXA) scan as part of a university clinical trial. Twin 1 had only menstruated twice since menarche; Twin 2 had not yet started menstruating. Both twins acknowledged suffering from disordered eating for approximately 3 years. Both twins presented with low lumbar spine bone mineral density (BMD) and normal total body, total hip, and femoral neck BMD. Diagnosis: Female athlete triad comprising disordered eating with insufficient energy availability, amenorrhea, and low age-related BMD. Management: Despite some weight gain and reduction of athletic training and competition over a 5-year period, lumbar BMD remained low in both twins and was complicated by a rapid decline in BMD at the hips. Twin 2 remained amenorrheic. The oral contraceptive pill was not effective in maintaining BMD in the other twin. Contraindicated treatment with bisphosphonates was not tolerated and promptly ceased. This case seminar emphasizes the absence of a clear physician-coordinated multi-disciplinary treatment approach and the complexity in treating all the components of the triad in young athletes.